O gerúndio na expressão de tempo futuro na diversidade do português do manauara - Simas, Ana Augusta de Oliveira (2016)
In Brazilian Portuguese, the occurrence of the gerund to express futurity has gotten the attention of studious who seek to record and analyze the variation and linguistics change in the scope of the Portuguese language. In this perspective of study, it is investigated the occurrence of the gerund in the expression of the future in the diversity of manauara Portuguese. Based on Sociofunctionalist theory that converges principles of Variationist Sociolinguistics and Linguistics Functionalism Tavares (2013) and Castillo (2012), it has as an object of analysis the gerundive construction coded by three verbs 'go + be + gerund' as an indication of future tense, in order to verify in which contexts it occurs and what factors contribute for the use of this variant. The analysis corpus is constituted of representative texts of the modalities of forms and speech, distributed in a continuum of degrees of monitoring that it was extended from the most formal to the less formal. About Writing, two journals from the city of Manaus were analyzed, the newspaper "A crítica" and "O Diário do Amazonas" and chats, messages and comments written by users on the Facebook page from one of the local television programs and from interactions made between teachers and academics in a group of WhatsApp application. About Speech, interactions areexamined in more formal and less formal contexts from speaking teachers, shop attendants, beyond records of spontaneous speech collected in manuara’s daily life. The constituted corpus and received statistical treatment through the GoldVarbX program, analyzing the following groups of factors as favorer or occurrence inhibitors of gerundive periphrasis on study. The Linguistic: I) Dependent Variable: a) gerundismo, b) non-gerundismo; II) types of verb: help: go (present); III) modal: can; with indication of certainty; 2. with no indication of certainty; 3. with indication of doubt; IV Marks of future tense: a) presence of the mark (adverb of time, locution headed by the preposition 'in', locution not headed by the preposition 'in'), b) no mark; V) Types of Clause: a) absolute clause; b) main clause, c) subordinate clause, d) independent clause and) interrogative clause; VI) Person of Speech: a) the first person singular; b) second-person singular; c) third person singular; d) first person plural and e) third plural. The results showed that the periphrasis 'go + be + gerund is more restricted to speech and occurs both in more formal contexts of interaction than less formal. The favorer factors of this gerundive construction are the absence of time mark, future indicator and coordinate clauses. Key-Words: Gerund; future; manauara Portuguese.